An e-Delphi Study on Software Virtualization in the Medical Diagnosis Process: The Experts’ Perspective - Ramsey, Byrian L. (European Scientific Journal, ESJ, 2020)
The purpose of this qualitative e-Delphi study was to collect opinions and experiences from a group of expert panel members made up of physicians and virtualization experts. This e-Delphi research study provided information about the opinions and experiences from experts about the possible benefits for virtualization in medical facilities. The expert panel was comprised of 12 virtualization experts and physicians. Virtualization is a concept of technology where one physical hardware device, called a server, is configured with software that allows for multiple software servers to be installed or implemented. Virtualization may offer benefits to healthcare organizations including the ability to deliver patient data to physicians more quickly. Virtualization has demonstrated substantial benefits in many areas of information technology infrastructure in the medical informatics field. The expert panel members were chosen at random through existing professional relationships and previous employment. The expert panel members were provided three rounds of survey questions and were asked to complete all surveys in its entirety. The findings show that hospitals and medical facilities will benefit from virtualization and provide increased patient care by delivering faster data to the patient and physician. As leaders in hospitals and medical facilities continue to be well-informed, leaders will be better equipped to make more-informed decisions about virtualization and the positive relationship software virtualization has on patient care.